Coronary Artery Bypass Grafting (CABG) After Failed Percutaneous Coronary Intervention (PCI): Integrative Review - Krzyszczak, Piotr; Wnuk, Aleksandra; Krzak, Michał; Kurpiel, Monika; Kulig, Piotr; Ożóg, Krzysztof (Quality in Sport, 2026)
Background. The dynamic development of interventional cardiology and the widespread use of drug-eluting stents (DES) have made percutaneous coronary intervention (PCI) the first-line treatment for many forms of coronary artery disease. However, phenomena such as in-stent restenosis (ISR), late stent thrombosis and the natural progression of multivessel atherosclerosis contribute to a growing population of patients requiring a shift toward surgical treatment (prior-PCI patients). Coronary artery bypass grafting (CABG) remains the gold standard for managing advanced coronary artery disease, including cases of failed prior percutaneous interventions. Aim. The aim of this study is to review the literature regarding the outcomes of CABG following failed PCI and to assess the impact of this surgical procedure on patient health and survival. Material and methods. A literature review (2016–2026) was conducted using the PubMed database, focusing on CABG procedures performed after prior PCI. An integrative approach was used to evaluate clinical outcomes, baseline risk factors, complication rates and duration of hospitalization. Results. Research findings suggest that patients undergoing CABG after prior PCI present with a significantly higher baseline operative risk, more complex coronary anatomy and a higher burden of comorbidities, particularly diabetes, compared to primary CABG patients. Although a history of multiple PCIs is associated with technically more demanding surgeries and a slightly increased risk of postoperative complications, CABG consistently provides superior long-term survival and lower rates of repeat revascularization. Conclusions. The analysis highlights that despite the increased baseline clinical risk, CABG remains a highly effective, safe and definitive salvage strategy for patients with exhausted percutaneous options. Careful qualification by a multidisciplinary Heart Team is essential in this high-risk group.